Unequal segregation of mitochondria during asymmetric cell division contributes to cell fate divergence in sister cells in vivo - Ioannis Segos; Jens Van Eeckhoven; Simon Berger; Nikhil Mishra; Eric J. Lambie; Barbara Conradt (Nature Communications)
Abstract The unequal segregation of organelles has been proposed to be an intrinsic mechanism that contributes to cell fate divergence during asymmetric cell division; however, in vivo evidence is sparse. Using super-resolution microscopy, we analysed the segregation of organelles during the division of the neuroblast QL.p in C. elegans larvae. QL.p divides to generate a daughter that survives, QL.pa, and a daughter that dies, QL.pp. We found that mitochondria segregate unequally by density and morphology and that this is dependent on mitochondrial dynamics. Furthermore, we found that mitochondrial density in QL.pp correlates with the time it takes QL.pp to die. We propose that low mitochondrial density in QL.pp promotes the cell death fate and ensures that QL.pp dies in a highly reproducible and timely manner. Our results provide in vivo evidence that the unequal segregation of mitochondria can contribute to cell fate divergence during asymmetric cell division in a developing animal.